1994
DOI: 10.1136/pgmj.70.826.536
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils in the 1990s: New perspectives on their role in health and disease

Abstract: Summary Eosinophils are characterized by their unique crystalloid granules that contain four basic proteins--MBP, ECP, EDN and EPO. The cell has many common features with neutrophils but, unlike that cell type, eosinophils utilize VLA-4/VCAM-1 as an adherence pathway and have a number of other receptors not shared by neutrophils. These include recognition units for IgE (distinct from CD23), and receptors for IL-5, IL-3 and RANTES. Following stimulation with a variety of agents, eosinophils prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
15

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 126 publications
2
68
0
15
Order By: Relevance
“…The occurrence of peripheral blood eosinophilia in patients with human immunodeficiency type 1 (HIV-1) infection has been described previously (1)(2)(3)(4). Our daily clinical work suggested that eosinophilia is more common in late-stage infection.…”
Section: Eosinophilia In Patientsmentioning
confidence: 65%
“…The occurrence of peripheral blood eosinophilia in patients with human immunodeficiency type 1 (HIV-1) infection has been described previously (1)(2)(3)(4). Our daily clinical work suggested that eosinophilia is more common in late-stage infection.…”
Section: Eosinophilia In Patientsmentioning
confidence: 65%
“…Both cell types are key effector cells in host defence against infections and they contain and can, upon activation, secrete a large and varied armoury of cytotoxic and degenerative enzymes [1,2]. Eosinophils are most commonly involved in parasitic infections and allergic inflammation, where eosinophilia is a prevalent indication of late-phase allergic inflammation causing tissue damage and asthma severity [3]. Neutrophils, on the other hand, are mainly involved in bacterial infections and other inflammatory reactions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Whatever its cause, eosinophil accumulation is deleterious and may in itself have pathological consequences as a result of local release of toxic substances, including cationic proteins, enzymes, reactive oxygen species, proinflammatory cytokines and arachidonic acid-derived factors (6).…”
Section: Pathobiology Of Hypereosinophiliamentioning
confidence: 99%
“…Eosinophils are derived from myeloid progenitors (GEMM-CFU) in bone marrow, through the action of three hematopoietic cytokines, GM-CSF, interleukin (IL)-3, and IL-5, among which only the latter is specific for eosinophil differentiation (6). Mature eosinophils are released into the blood stream and rapidly migrate to peripheral tissues, namely gut and bronchial mucosae and skin, where survival is short unless apoptosis is prevented by factors such as IL-3, IL-5, and/or GM-CSF.…”
Section: Pathobiology Of Hypereosinophiliamentioning
confidence: 99%